PERAN GURU SEJARAH KEBUDAYAAN ISLAM DALAM UPAYA PEMBENTUKKAN KARAKTER TERPUJI TERHADAP SISWA DI MA AL MUKMIN TEMBARAK - Mujib santoso; Abdul Malik (As-Sulthan Journal of Education, 2025)
This study aims to examine the role of teachers in the implementation of Islamic Cultural History education in shaping students' character at MA Al Mukmin Tembarak. The research employs a qualitative approach, with the subjects consisting of Islamic Cultural History teachers and eleventh-grade students. Data were collected through observations, interviews, and documentation. The data analysis process involved data reduction, data presentation, and drawing conclusions. The findings of the study reveal that the role of the Islamic Cultural History teacher at MA Al Mukmin Tembarak is crucial in shaping students' character. The teacher acts as a partner, resource, and mentor. The teacher not only imparts values of Islamic Cultural History but also guides students in practicing good ethics and manners in their interactions. Additionally, the teacher emphasizes the importance of mutual respect and appreciation of differences, while providing positive role models. In the lessons, the teacher conveys moral messages from the Khulafaurrasyidin, including moral enhancement, spreading love, and contributing positively to society. The teacher also shares inspirational messages from local heroes that are relevant to students' daily lives, fostering a sense of patriotism and social responsibility. Thus, the role of the Islamic Cultural History teacher at MA Al Mukmin Tembarak significantly contributes to the development of students' character as religious, honest, and socially responsible individuals.